Titanium diboride particle reinforced a205x aluminum matrix composite and method of making

CN121294968BActive Publication Date: 2026-10-30HUZHOU HEZHUTAI INTELLIGENT TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511728475.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2026-10-30
Estimated Expiration
2045-11-24

AI Technical Summary

Technical Problem

然而,这些方法通常设备成本高昂、工艺复杂且生产规模受限,难以满足大规模工业生产的需要

Benefits of technology

[0049]和现有技术相比,本发明技术方案以Al-Cu-Mg-Ag合金为基体,以原位自生TiB2颗粒为增强体,通过元素Sc、Y、La、Mn、Zr、Ni、V的添加,借助颗粒的位错强化作用,减小了Al3Sc、Al3Zr、AlNiCu、AlV析出相的尺寸,并促进其在材料基体内的均匀分布,与晶内分布的TiB2颗粒一同作用提高材料的常温与高温性能。同时颗粒限制了AlMn、AlY、AlLa、AlV等第二相在晶界的尺寸,使其成为微米级第二相,阻碍了晶界在高温时的滑动,从而提高晶界的高温强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121294968B_ABST
    Figure CN121294968B_ABST
Patent Text Reader

Abstract

Titanium diboride particle reinforced A205X aluminum matrix composite material and preparation method thereof, belong to the technical field of aluminum alloy material. The composite material is composed of the following components in percentage by mass: Cu: 4.2~5.2%, Mg: 0.25~0.5%, Ag: 0.4~0.8%, Sc: 0.005~0.2%, Y: 0.005~0.2%, La: 0.005~0.2%, Mn: 0.005~0.15%, Zr: 0.005~0.2%, Ni: 0.005~0.2%, V: 0.005~0.2%, Ti: 0.15~3.0%, B: 0.005~1.5%, Fe: 0.01~0.08%, inevitable impurities and the balance of Al. The composite material has the characteristics of high strength and high temperature resistance, and can guarantee considerable mechanical properties even at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aluminum alloy materials technology, specifically relating to a high-strength, high-temperature resistant titanium diboride particle-reinforced A205X aluminum matrix composite material and its preparation method. Background Technology

[0002] As a new generation of high-performance structural materials, particle-reinforced aluminum matrix composites significantly improve the strength, elastic modulus, wear resistance and high-temperature performance of aluminum alloys by introducing ceramic particles (such as SiC, TiB2, etc.), and have become an important choice for high-end equipment such as aerospace, automotive industry and precision instruments.

[0003] However, these materials have long faced a key bottleneck in performance improvement: while the strength and hardness of the material improve with the introduction of reinforcing particles, the plasticity, especially elongation, often deteriorates simultaneously. The root cause of this contradiction lies in the difficulty of optimizing the distribution of reinforcing particles in the aluminum matrix—in the traditional casting process, reinforcing particles are prone to agglomerate at grain boundaries, forming stress concentration points, and simultaneously interfering with the distribution and morphology of second phases such as eutectic silicon, thus severely impairing the material's toughness and deformability.

[0004] Among existing preparation technologies, rapid solidification techniques such as powder metallurgy (including high-energy ball milling) and additive manufacturing (such as selective laser melting) can improve the uniformity of particle distribution to some extent by suppressing interfacial migration of reinforcing particles. However, these methods are typically expensive, complex, and limited in production scale, making them difficult to meet the needs of large-scale industrial production. In contrast, traditional forming methods such as gravity casting, low-pressure casting, and high-pressure die casting are characterized by low cost, high efficiency, and suitability for large-scale production of complex components. However, they still lack efficient and stable technical solutions to address the problem of uniform distribution of reinforcing particles, resulting in composite materials with often unsatisfactory plasticity.

[0005] Especially for aluminum-copper alloys that pursue high strength and high heat resistance (such as ZL205A), and cast aluminum-copper alloys with Al-Cu-Mg-Ag matrix, the former involves environmentally unfriendly heavy metal elements (such as cadmium), while the latter's strength is difficult to fully meet the current requirements for high-strength and high-toughness aluminum alloys in lightweight applications. Although in-situ self-generated titanium diboride (TiB2) particles can achieve good interfacial bonding between the reinforcement and the aluminum matrix, TiB2 particles are also prone to migration and enrichment at grain boundaries during melt solidification, which deteriorates the ductility of the material. Therefore, developing a technology suitable for traditional casting processes that can effectively control the distribution of reinforcement particles is of great significance for achieving high-strength and high-toughness aluminum-copper alloys. Summary of the Invention

[0006] This application further improves the formulation of the composite material to solve the aforementioned technical problems. One objective of this invention is to provide a titanium diboride particle-reinforced A205X aluminum-based composite material, and another objective is to provide a method for preparing this composite material.

[0007] The specific technical solution is explained below:

[0008] Titanium diboride particle-reinforced A205X aluminum matrix composite material, by mass percentage, consists of the following components:

[0009] Cu: 4.2~5.2%, Mg: 0.25~0.5%, Ag: 0.4~0.8%, Sc: 0.005~0.2%, Y: 0.005~0.2%, La: 0.005~0.2%, Mn: 0.005~0.15%, Zr: 0.005~0.2%, Ni: 0.005~0.2%, V: 0.005~0.2%, Ti: 0.15~3.0%, B: 0.005~1.5%, Fe: 0.01~0.08%, unavoidable impurities and balance Al.

[0010] In the above technical solution, the functions of each component are as follows:

[0011] Cu, as one of the main strengthening elements, together with Mg, forms precipitates such as Al2CuMg, which improves the hardness and strength of the material. Within the above range, the strengthening effect can be ensured, while avoiding excessive Cu from causing hot cracking and corrosion sensitivity.

[0012] Mg can promote the formation of Al2CuMg and Al2Cu-based strengthening phases, and within the above-mentioned range, both strength and corrosion resistance can be taken into account.

[0013] Ag can promote the formation of high-density Ω phase during heat treatment, improving the high-temperature performance of materials. However, excessive Ag content will increase costs and coarsen the precipitated phase.

[0014] Sc and Zr can form Al3Sc and Al3Zr nano-dispersed phases, which have a strong grain refinement effect and improve high-temperature stability and creep resistance.

[0015] Y and La, as rare earth elements, refine the microstructure, purify the melt, improve the solidification structure, and increase the elongation.

[0016] Mn alters the morphology of the Fe phase, reducing brittleness.

[0017] Ni can improve high-temperature strength.

[0018] V helps refine grains and stabilize precipitates, thus improving overall mechanical properties.

[0019] Ti and B undergo an in-situ reaction to generate TiB2 particles, which refine the grain size and provide dispersion strengthening. Within the aforementioned range, a fine and uniform particle distribution can be obtained, avoiding particle agglomeration and material embrittlement caused by excessive hard phase.

[0020] When the Fe content is high, it becomes a harmful substance that can form a brittle needle-like phase. It should be kept at a low level to ensure the toughness and corrosion resistance of the material.

[0021] In a preferred embodiment, the mass ratio of Cu to Mg is (10~17):1, at which a relatively ideal strength can be obtained.

[0022] In a preferred embodiment, the mass ratio of Ti to B is (2~30):1. At this ratio, the enhancement effect can be obtained while avoiding material catalysis and ensuring the toughness of the material.

[0023] In a preferred embodiment, the Fe content is ≤0.05%.

[0024] In a preferred embodiment, at room temperature, the yield strength is >480MPa, the tensile strength is >520MPa, and the elongation is >5.0%.

[0025] In a further preferred embodiment, at a temperature of 300°C, the yield strength is >300MPa, the tensile strength is >350MPa, and the elongation is >20.0%.

[0026] The preparation method of titanium diboride particle-reinforced A205X aluminum matrix composite material includes the following steps:

[0027] Melting: Except for raw materials containing Ti and B, place all component raw materials in a crucible furnace and heat to 760~780℃ to completely melt and remove slag;

[0028] In-situ reaction: At 780~800℃, raw materials containing Ti and B are added to the melt and stirred to generate TiB2 particles in situ and disperse them.

[0029] Refining and degassing: reduces oxidation and hydrogen content;

[0030] Casting: Reduce the temperature to 720~740℃, pour into a preheated mold, and let cool;

[0031] Heat treatment: This involves solution treatment and age hardening of the cooled material.

[0032] In a preferred embodiment, the raw material components are added in the following manner:

[0033] Cu: elemental or Al-50Cu (representing an alloy of aluminum and copper, where the number "50" indicates the mass percentage of copper content, the same below) intermediate alloy;

[0034] Mg: elemental or Al-20Mg master alloy;

[0035] Ag: Elemental form or Al-20Ag master alloy;

[0036] Sc: Al-2Sc master alloy;

[0037] Y: Al-10Y master alloy;

[0038] La: Al-10La master alloy;

[0039] Mn: Al-10Mn or Al-20Mn master alloy;

[0040] Zr: K2ZrF6 or Al-5Z or Al-10Zr master alloy;

[0041] Ni: elemental or Al-20Ni master alloy;

[0042] V: Al-5V or Al-10V master alloy;

[0043] Ti: Potassium fluorotitanate or Al-10Ti master alloy;

[0044] B: Potassium fluoroborate or Al-5B master alloy;

[0045] Fe: Al-20Fe or Al-50Fe master alloy.

[0046] In a preferred embodiment, in the in-situ reaction step, K2TiF6 and KBF4 are premixed at a mass ratio of (2~2.4):1 and then added to the melt after premixing.

[0047] In a preferred embodiment, the heat treatment step involves solution treatment at 540±30℃ for 6-8 hours followed by water quenching; the aging strengthening treatment involves treatment at 160±20℃ for 8-12 hours.

[0048] In summary, the technical solution described in this invention has the following main beneficial effects:

[0049] Compared with existing technologies, the technical solution of this invention uses an Al-Cu-Mg-Ag alloy as the matrix and in-situ self-generated TiB2 particles as reinforcement. Through the addition of elements Sc, Y, La, Mn, Zr, Ni, and V, the dislocation strengthening effect of the particles reduces the size of Al3Sc, Al3Zr, AlNiCu, and AlV precipitates and promotes their uniform distribution within the material matrix. These precipitates, together with the intragranular TiB2 particles, improve the material's performance at both room temperature and high temperature. Simultaneously, the particles restrict the size of second phases such as AlMn, AlY, AlLa, and AlV at grain boundaries, making them micron-sized second phases. This hinders grain boundary sliding at high temperatures, thereby improving the high-temperature strength of the grain boundaries.

[0050] Further or more detailed beneficial effects will be described in conjunction with specific embodiments in the detailed implementation. Attached Figure Description

[0051] Figure 1 This is a photograph showing TiB2 particles within the crystal in Example 1;

[0052] Figure 2 This is a photograph showing the second phase at the grain boundary in Example 1;

[0053] Figure 3 These are photographs showing the intracrystalline precipitates and TiB2 particles in Example 1;

[0054] Figure 4 This is another photograph showing the second phase at the grain boundary in Example 1. Detailed Implementation

[0055] The present invention will be further explained in conjunction with the embodiments:

[0056] The core technical problem faced by the technical solution of this application embodiment stems from the inventor's accurate understanding of the prior art. Therefore, how to improve the toughness and elongation of titanium diboride (TiB2) particle-reinforced A356 aluminum matrix composite material is a technical problem that the inventor urgently needs to solve.

[0057] It should be noted that the embodiments do not constitute a limitation on the scope of protection of the claims of this invention. All technical solutions that can be reasonably expected by those skilled in the art based on the technical concepts provided / proved by the embodiments should be covered within the scope of protection of the claims of this invention.

[0058] The specific implementation examples are detailed below:

[0059] Example 1 This embodiment relates to a TiB2 particle-reinforced A205X aluminum matrix composite material, which, by mass percentage, consists of the following components:

[0060] Cu: 4.2%, Mg: 0.25%, Ag: 0.4%, Sc: 0.005%, Y: 0.005%, La: 0.005%, Mn: 0.005%, Zr: 0.005%, Ni: 0.005%, V: 0.005%, Ti: 0.15%, B: 0.005%, Fe: 0.01%, unavoidable impurities and balance Al.

[0061] Example 2 This embodiment relates to a TiB2 particle-reinforced A205X aluminum matrix composite material, which, by mass percentage, consists of the following components:

[0062] Cu: 5.2%, Mg: 0.5%, Ag: 0.8%, Sc: 0.2%, Y: 0.2%, La: 0.2%, Mn: 0.15%, Zr: 0.2%, Ni: 0.2%, V: 0.2%, Ti: 3.0%, B: 1.5%, Fe: 0.08%, unavoidable impurities and balance Al.

[0063] Example 3 This embodiment relates to a TiB2 particle-reinforced A205X aluminum matrix composite material, which, by mass percentage, consists of the following components:

[0064] Cu: 4.6%, Mg: 0.35%, Ag: 0.6%, Sc: 0.1%, Y: 0.1%, La: 0.1%, Mn: 0.1%, Zr: 0.1%, Ni: 0.1%, V: 0.1%, Ti: 1.5%, B: 0.7%, Fe: 0.05%, unavoidable impurities and balance Al.

[0065] The preparation methods of TiB2 particle-reinforced A2O5X aluminum matrix composites in Examples 1-3 are as follows:

[0066] First, according to the formula, all components except Ti and B raw materials are placed in a crucible furnace and heated to 760~780℃ to completely melt and remove slag. The state of each component is as follows: Al-50Cu, Al-20Mg, Al-20Ag, Al-2Sc, Al-10Y, Al-10La, Al-10Mn, K2ZrF6, Al-20Ni, Al-5V and Al-20Fe.

[0067] Then, at 780~800℃, K2TiF6 and KBF4 premixed at a mass ratio of about 2.2:1 are slowly added to the melt, and mechanically stirred at 200~300rpm for 8~12 minutes to allow TiB2 particles to be generated in situ and dispersed.

[0068] Use a covering agent or argon to blow for 3-5 minutes to reduce the content of oxidation and hydrogen.

[0069] Reduce the temperature to 720~740℃, pour into a preheated mold, and allow to cool naturally.

[0070] The cooled material was solution treated at approximately 540°C for 7 hours, followed by water quenching and then artificial aging at approximately 160°C for 10 hours to optimize the strengthening phase and stabilize the particles.

[0071] Comparative Example 1: Domestically available ZL205A aluminum alloy.

[0072] Comparative Example 2: International A201 Alloy.

[0073] The mechanical properties of the composite materials in Examples 1-3 and Comparative Examples 1-2 were tested and are shown in Table 1 below:

[0074] Table 1 Mechanical property parameters of the composite materials corresponding to Examples 1-3 and Comparative Examples 1-2 Example 1 480 520 10 300 350 28 Example 2 520 560 5 360 400 20 Example 3 500 540 8 330 360 23 Comparative Example 1 400 470 3 210 290 6 Comparative Example 2 440 480 5 280 310 7 .

[0075] In Table 1, the yield strength, tensile strength and elongation at room temperature are tested using the static uniaxial tensile test specified in GB / T 228.1, and the yield strength, tensile strength and elongation at 300℃ are tested using the static uniaxial tensile test specified in GB / T 228.1.

[0076] Depend on Figures 1-4 As can be seen, the TiB2 particle-reinforced A205X aluminum matrix composite material prepared in Example 1 has a small precipitated phase size and a micron-sized second phase at the grain boundary, thus exhibiting good grain boundary strength at both room temperature and high temperature.

[0077] As shown in Table 1, the composite materials corresponding to Examples 1-3 can maintain a yield strength of over 480 MPa and a tensile strength of over 520 MPa at room temperature, with an elongation of ≥5%; at 300℃, the yield strength can also maintain a yield strength of over 300 MPa, a tensile strength of over 350 MPa, and an elongation of ≥20%.

[0078] Compared with Comparative Examples 1-2, the yield strength, tensile strength and elongation of Examples 1-3 were improved to varying degrees, and the elongation at high temperature was significantly improved.

[0079] This is because the TiB2 particle-reinforced A205X aluminum matrix composites prepared in Examples 1-3 have the following improvements:

[0080] The small and uniform particle size of TiB2 particles results in strong interfacial bonding, effectively pinning dislocations and stabilizing grains, while maintaining material strength at high temperatures.

[0081] Rare earth elements such as Sc, Y, and La form a stable dispersed phase, which refines the grains, purifies the matrix, and improves the elongation and high-temperature performance of the material.

[0082] The optimized Cu–Mg–Ag ratio can form a precipitated strengthening phase with excellent heat resistance, and the strengthening effect can be sustained at high temperatures;

[0083] In the embodiments, the mass ratio of Cu to Mg is controlled at (10~17):1, and the mass ratio of Ti to B is controlled at (2~30):1, so as to balance the strength and toughness of the material under normal temperature / high temperature environment.

[0084] The synergistic effect of Ti, Zr, and V refines the microstructure and inhibits high-temperature grain boundary slip.

[0085] It reduces the formation of brittle phases such as Fe, decreases fracture sources, and improves ductility.

[0086] In the description of this specification, the references to terms such as "embodiment," "basic embodiment," "preferred embodiment," "other embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0087] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.

[0088] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A titanium diboride particle-reinforced A205X aluminum matrix composite material, characterized in that: It consists of the following components by mass percentage: Cu: 4.2~5.2%, Mg: 0.25~0.5%, Ag: 0.4~0.8%, Sc: 0.005~0.2%, Y: 0.005~0.2%, La: 0.005~0.2%, Mn: 0.005~0.15%, Zr: 0.005~0.2%, Ni: 0.005~0.2%, V: 0.005~0.2%, Ti: 0.15~3.0%, B: 0.005~1.5%, Fe: 0.01~0.08%, unavoidable impurities and balance Al; The mass ratio of Cu to Mg is (10~17):1; The mass ratio of Ti to B is (2~30):1; At room temperature, the yield strength is >480MPa, the tensile strength is >520MPa, and the elongation is >5.0%. At 300℃, the yield strength is >300MPa, the tensile strength is >350MPa, and the elongation is >20.0%.

2. The composite material according to claim 1, characterized in that: The Fe content is ≤0.05%.

3. The method for preparing the titanium diboride particle-reinforced A205X aluminum-based composite material according to claim 1 or 2, characterized in that: The steps include the following: Melting: Except for raw materials containing Ti and B, place all component raw materials in a crucible furnace and heat to 760~780℃ to completely melt and remove slag; In-situ reaction: At 780~800℃, raw materials containing Ti and B are added to the melt and stirred to generate TiB2 particles in situ and disperse them. Refining and degassing: reduces oxidation and hydrogen content; Casting: Reduce the temperature to 720~740℃, pour into a preheated mold, and let cool; Heat treatment: This involves solution treatment and age hardening of the cooled material.

4. The preparation method according to claim 3, characterized in that: The raw material components are added in the following ways: Cu: elemental or Al-50Cu master alloy; Mg: elemental or Al-20Mg master alloy; Ag: Elemental form or Al-20Ag master alloy; Sc: Al-2Sc master alloy; Y: Al-10Y master alloy; La: Al-10La master alloy; Mn: Al-10Mn or Al-20Mn master alloy; Zr: K2ZrF6 or Al-5Z or Al-10Zr master alloy; Ni: elemental or Al-20Ni master alloy; V: Al-5V or Al-10V master alloy; Ti: Potassium fluorotitanate or Al-10Ti master alloy; B: Potassium fluoroborate or Al-5B master alloy; Fe: Al-20Fe or Al-50Fe master alloy.

5. The preparation method according to claim 3, characterized in that: In the in-situ reaction step, K2TiF6 and KBF4 are premixed at a mass ratio of (2~2.4):1 and then added to the melt after premixing.

6. The preparation method according to claim 3, characterized in that: In the heat treatment process, the solution treatment is carried out at 540±30℃ for 6~8 hours, followed by water quenching. The aging intensification treatment was carried out at 160±20℃ for 8~12 hours.

Citation Information

Patent Citations

  • Sc-Ni-RE high-strength heat-resistant aluminium alloy material and preparation method thereof

    CN102021429A

  • Heat-resistant cyclic wear-resistant aluminum-based composite material and preparation method thereof

    CN120443027A